Marvel Comics library Amazing Spider-Man: Vol. 1. 1962–1964 - Lee, Stan 1922-2018; Ditko, Steve 1927-2018 (Taschen, 2021)
This XXL-sized collector's dream, close in size to the original artworks, features the first 21 stories of the world's favorite web slinger from 1962-1964. Rather than recolor the original artwork (as has been done in previous decades' reprints of classic comics), Taschen has attempted to create an ideal representation of these books as they were produced at the time of publication. The most pristine pedigreed comics have been cracked open and photographed for reproduction in close collaboration with Marvel and the Certified Guaranty Company. Each page has been photographed as printed more than half a century ago, then digitally remastered using modern retouching techniques to correct problems with the era's inexpensive, imperfect printing--as if hot off of a world-class 1960s printing press. Three different paper stocks, including an uncoated and woodfree paper, were exclusively developed for this series to simulate the feel of the original comics. With an in-depth historical essay by Marvel editor Ralph Macchio, an introduction by uber-collector David Mandel, and original art, rare photographs, and other gems, these 697 pages of wall-crawling wonder will make anyone's spider-sense tingle with anticipation
Limited edition of 5000 numbered copies
Keywords: Spider-Man -- Fiktive Gestalt; Spider-Man / (Fictitious character) / Comic books, strips, etc / History; Science fiction comic books, strips, etc / History and criticism; Spider-Man / (Fictitious character); Science fiction comic books, strips, etc; Criticism, interpretation, etc; Comic